Feasibility and Patient-Reported Outcomes of Full-Body Red and Near-Infrared Photobiomodulation for Musculoskeletal Pain in a Predominantly Hispanic/Latino Population: A Single-Arm Pilot Study - Robson Dias Scoz; Frida Garza; Ivana Burberg; Isabella Moreno; Melissa Espinosa Cantu; Mia Dominguez; Juan Gonzalez (Photobiomodulation, Photomedicine, and Laser Surgery, 2026)
Objective: To characterize feasibility, tolerability, and patient-reported outcomes after a 10-session full-body red and near-infrared photobiomodulation (PBM) protocol for musculoskeletal pain in a predominantly Hispanic/Latino community sample. Background: PBM is a non-pharmacological intervention with potential analgesic and anti-inflammatory effects. Evidence from community-based and Hispanic/Latino populations remains limited, and full-body LED protocols are incompletely standardized. Methods: This single-arm observational pilot study included 40 adults with self-reported acute or chronic musculoskeletal pain. Participants completed baseline and post-protocol Qualtrics surveys. The intervention used a full-body LED panel emitting 630, 660, 830, and 850 nm light in continuous-wave mode for 20 min per session, across 10 sessions. Forty baseline and post-protocol records were deliberately paired and verified by the research team. Outcomes included global and regional perceived pain improvement, functional domains, acceptability, and safety. An exploratory paired analysis used conservatively estimated post-intervention regional pain scores because the same ordinal intensity scale was not directly repeated after treatment. Results: Participants had a mean age of 37.2 years (SD 19.9); 62.5% were female and 87.5% identified as Hispanic/Latino. Global improvement was reported by 35/38 respondents (92.1%; 95% CI, 78.6−98.3%), immediate pain relief after the first session by 26/35 (74.3%; 95% CI, 56.7−87.5%), and willingness to recommend PBM by 38/40 (95.0%; 95% CI, 83.1−99.4%). Functional improvement ranged from 60.0% for sleep quality to 82.5% for muscle stiffness and energy. Exploratory estimated total pain burden decreased from a median of 6.0 (IQR, 2.0–12.5) to 3.5 (IQR, 1.0–9.0; p < 0.001; r = 0.88). One participant reported a negative or uncomfortable feeling; event severity and duration were not captured. Conclusions: Full-body red/NIR PBM was feasible and highly acceptable in this community sample and was associated with substantial perceived benefit. The uncontrolled design, non-validated survey outcomes, and estimated rather than directly measured post-intervention pain scores preclude efficacy conclusions. These findings support a sham-controlled trial using validated, directly repeated outcome measures and prospectively calibrated dosimetry.